2016
DOI: 10.1103/physrevlett.116.188303
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Osmotic Flow in Thin Films

Abstract: We report on the first micro-scale observation of the velocity field imposed by a non-uniform heat content along the solid/liquid boundary. We determine both radial and vertical velocity components of this thermo-osmotic flow field by tracking single tracer nanoparticles. The measured flow profiles are compared to an approximate analytical theory and to numerical calculations. From the measured slip velocity we deduce the thermo-osmotic coefficient for both bare glass and Pluronic F-127 covered surfaces. The v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
174
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(189 citation statements)
references
References 38 publications
14
174
1
Order By: Relevance
“…The novel result concerns the thermoelectric contribution to (35), that is, the first term proportional to the electrolyte Seebeck coefficient S. The remaining term T µ and that e µ are known as thermo-osmosis [5,26], whereas the last one, n µ , is similar to salt osmosis [36,37]. As a main finding of this work, we note that v s does not depend on the electrical conductivity of the particle surface.…”
Section: Thermodynamic Forces and Slip Velocitymentioning
confidence: 71%
See 3 more Smart Citations
“…The novel result concerns the thermoelectric contribution to (35), that is, the first term proportional to the electrolyte Seebeck coefficient S. The remaining term T µ and that e µ are known as thermo-osmosis [5,26], whereas the last one, n µ , is similar to salt osmosis [36,37]. As a main finding of this work, we note that v s does not depend on the electrical conductivity of the particle surface.…”
Section: Thermodynamic Forces and Slip Velocitymentioning
confidence: 71%
“…Then s corresponds to the charge per unit area of the surface, which exactly cancels that of the diffuse layer. On the contrary, the main results of the present paper are derived from equation (10), with the outer boundary condition determined by the thermoelectric far-field (5). This implies that σ as defined in (10) contains counterions and thermocharge, and thus does no longer define the surface charge density.…”
Section: Boundary Layer Approximationmentioning
confidence: 81%
See 2 more Smart Citations
“…In that context, Ganti et al [32] have explored three different methods to characterize thermo-osmosis using molecular simulations, and they found that all methods yield very similar results. Bregulla et al [33] reported the first microscale observation of the velocity field imposed by a nonuniform temperature and deduced the thermo-osmosis coefficient for different surfaces. Nevertheless, the role of surface wettability and interfacial hydrodynamics have hardly been discussed so far.…”
mentioning
confidence: 99%